Structured approach in improving weekend handovers in a medical high dependency unit. Issue 1 (26th August 2014) - Patel, Roma; Thiagarajan, Prarthana
Abstract: Weekend admissions to hospital have been associated with adverse patient outcomes, including higher morbidity and mortality risk in general medicine and surgery. The reasons behind this are likely to be multifactorial and include reduced senior clinician-led care, decreased overall workforce, and ineffective or incomplete handover. With the advent of shift-work patterns, robust handover between medical teams is of paramount importance, particularly before weekends. This has been reflected in recent publications by Royal College of Physicians (acute care toolkit 1: handover, May 2011), that identified handover as an error-prone process and issued guidelines designed to optimise its effectiveness. The aim of this project was to evaluate weekend patient mortality and success of handover on the medical high dependency unit of a large teaching hospital in the United Kingdom, before and after introduction of a structured handover tool on Friday afternoons during May 2013. This unit is registrar-led at weekends. Weekend mortality decreased from 43% in March 2013 to 22% in May 2013 (odds ratio 0.37, 95% CI 0.19-0.68, p=0.07). Documentation of resuscitation status and escalation plans increased from 75% in March 2013 to 93% in May 2013. There was universal positive feedback from registrars involved with the handover tool, who provided senior cover during the weekends in May 2013. It is hoped that structured, written handover will ultimately become commonplace in this unit and will improve patient safety at weekends.